Nuclear energy, nuclear waste - Galperin, Anne. (New York : Chelsea House Publishers, 1992)
Discusses nuclear power and how the positive benefits of nuclear energy are balanced against the problem of disposing of radioactive wastes.
Includes bibliographical references (p. 102-103) and index.
Book Links (A.L.A.).
Booklist.
Wilson's Junior High School.
8.9
5-8
Keywords: Nuclear energy -- Juvenile literature; Nuclear power plants -- Juvenile literature; Radioactive waste disposal -- Juvenile literature; Nuclear energy; Nuclear power plants; Radioactive waste disposal; Nuclear energy; Nuclear power plants; Radioactive waste disposal